2006
DOI: 10.1002/lt.20652
|View full text |Cite
|
Sign up to set email alerts
|

Acute humoral rejection and C4d immunostaining in ABO blood type-incompatible liver transplantation

Abstract: Complement C4d deposition in graft capillaries has been reported to be associated with antibody-mediated rejection in kidney and other solid organ transplantation. The correlation of C4d deposits and humoral rejection in liver transplants, however, is not well understood. We investigated the C4d immunostaining pattern in 34 patients whose liver biopsy was taken within the first 3 postoperative weeks for suspected acute rejection after ABO blood type-incompatible liver transplantation. The staining pattern was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 21 publications
3
90
1
Order By: Relevance
“…The diagnosis of rejection in LT is usually confirmed by histologic findings; however, confirmation of the diagnosis of AMR is often difficult because there is no consensus for the histologic diagnostic criteria of AMR in ABOi LT. Staining with C4d, an immunohistochemical stain for a fragment of activated complement particle, may be a special finding of AMR in ABOi LT (12,13); however, C4d staining alone cannot be considered specific for the diagnosis of AMR because focal C4d deposits in the arteriolar wall can be found in approximately 30% of liver biopsies from normal livers. Diffuse endothelial or sinusoidal C4d deposition is a finding of AMR, but it can be found in other inflammatory processes such as chronic or acute LGIT, local graft infusion therapy; RIT, rituximab; SPL, splenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of rejection in LT is usually confirmed by histologic findings; however, confirmation of the diagnosis of AMR is often difficult because there is no consensus for the histologic diagnostic criteria of AMR in ABOi LT. Staining with C4d, an immunohistochemical stain for a fragment of activated complement particle, may be a special finding of AMR in ABOi LT (12,13); however, C4d staining alone cannot be considered specific for the diagnosis of AMR because focal C4d deposits in the arteriolar wall can be found in approximately 30% of liver biopsies from normal livers. Diffuse endothelial or sinusoidal C4d deposition is a finding of AMR, but it can be found in other inflammatory processes such as chronic or acute LGIT, local graft infusion therapy; RIT, rituximab; SPL, splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the C4d staining was quantitatively assessed by the percentage of portal tracts containing distinctly stained stroma and/or endothelium. Biopsies containing !50% stromal-positive portal tracts were considered positive (13). DIHBS was considered if there was evidence of multiple strictures and diffusely scattered dilatation of intrahepatic bile ducts on computed tomography without HA thrombosis.…”
Section: Diagnosis and Management Of Amrmentioning
confidence: 99%
“…26 Stromal positivity was recorded with or without endothelial staining. 20 Biopsies in which only vascular endothelium was stained were evaluated as endothelial-only positive. Staining involving 50% or more of the portal tracts was classified as diffuse, whereas less than 50% as focal.…”
Section: Evaluation Of C4d Immunostainingmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] In ABO-incompatible transplantation, our group reported that portal stromal C4d immunostaining was associated with a high postoperative titer of anti-A/B antibody and reduced graft survival, suggesting the association of C4d deposition and ABO-incompatible humoral rejection. 20 In this study, we focused on the role of C4d immunohistochemistry in ABO-identical/compatible liver allografts with reference to preformed alloantibodies evaluated by lymphocyte crossmatch tests. We also evaluated the pattern of C4d deposition and conventional morphology.…”
mentioning
confidence: 99%
“…The histologic changes suggestive of ABMR are typically a biliary-type pattern of injury, with increasing severity leading to evidence of microvascular injury (see Table 1). 90 The pattern of injury, particularly in cases of mild ABMR, is not specific and can be seen with bile duct obstruction, ischemic injury (primary versus ABMR induced), or acute rejection. Evaluation for C4d deposition by IHC can then potentially provide useful, supplemental information in the process of differentiating possible causes of the histologic or functional abnormalities.…”
Section: Livermentioning
confidence: 99%